More Than 50 Years of Successful Continuous Temperature Section Measurements by the Global Expendable Bathythermograph Network, Its Integrability, Societal Benefits, and Future - Goni, Gustavo J.; Sprintall, Janet; Bringas, Francis; Cheng, Lijing; Cirano, Mauro; Dong, Shenfu; Domingues, Ricardo; Goes, Marlos; Lopez, Hosmay; Morrow, Rosemary; Rivero, Ulises; Rossby, Thomas; et al. (Frontiers in Marine Science, 2019)
The first eXpendable BathyThermographs (XBTs) were deployed in the 1960s in the North Atlantic Ocean. In 1967 XBTs were deployed in operational mode to provide a continuous record of temperature profile data along repeated transects, now known as the Global XBT Network. The current network is designed to monitor ocean circulation and boundary current variability, basin-wide and trans-basin ocean heat transport, and global and regional heat content. The ability of the XBT Network to systematically map the upper ocean thermal field in multiple basins with repeated trans-basin sections at eddy-resolving scales remains unmatched today and cannot be reproduced at present by any other observing platform. Some repeated XBT transects have now been continuously occupied for more than 30 years, providing an unprecedented long-term climate record of temperature and geostrophic velocity profiles that are used to understand variability in ocean heat content, sea level change, and meridional ocean heat transport. Here, we present key scientific advances in understanding the changing ocean and climate system supported by XBT observations. Improvement in XBT data quality and its impact on computations, particularly of ocean heat content, are presented. Technology development for probes, launchers, and transmission techniques are also discussed. Finally, we offer new perspectives for the future of the Global XBT Network.